Investasi Infrastruktur Sumatera Barat dari Kontribusi Pendapatan Asli Daerah dan Dana Bagi Hasil - Dona, Elva (JURNAL PUNDI, 2024)
This study aims to analyze the contribution of Local Own-Source Revenue (PAD) and Revenue Sharing Funds (DBH) to infrastructure investment in regencies/cities in West Sumatra Province. Using panel data this study explores the relationship between regional fiscal variables and the allocation of capital expenditures for infrastructure development. The analytical methods employed include panel data regression with fixed effects and random effects to ensure the accuracy of the results.The findings show that PAD has a significant positive contribution to infrastructure investment, reflecting the local government's ability to optimize local revenue sources for development. Meanwhile, DBH also shows a positive impact, albeit with lower significance compared to PAD. These findings indicate that while fiscal transfers from the central government are important, strengthening the local revenue base plays a more dominant role in driving infrastructure investment.The study suggests the importance of managing and enhancing PAD as a key strategy in supporting regional infrastructure development. Additionally, it highlights the need for policies that promote efficiency and transparency in the use of DBH to yield a more significant impact on infrastructure development in West Sumatra.